1975
DOI: 10.1042/bj1470221
|View full text |Cite
|
Sign up to set email alerts
|

The actin content of fibroblasts

Abstract: Cultures of chick skin fibroblasts were dissolved in solutions of sodium dodecyl sulphate, and their entire protein content was examined by gel electrophoresis. The most abundant species migrated in the same position as muscle actin. It gave a similar pattern of iodinated peptides after reaction with radioactive sodium iodide and digestion with proteinases, and contained comparable amounts of N-methylhistidine. Its amount was estimated by quantitative densitometry of stained gels with bovine serum albumin as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 31 publications
5
43
1
Order By: Relevance
“…Bray and Thomas determined that as much as 50 % of the actin in extracts of brain is in a non-filamentous form under a variety of extraction conditions [36,37]. Recently we determined that in extracts of suspension cultured lymphocytes (cell line DG-75) as much as 60-65 o/, of the actin is in an unpolymerized form [39].…”
Section: Discussionmentioning
confidence: 99%
“…Bray and Thomas determined that as much as 50 % of the actin in extracts of brain is in a non-filamentous form under a variety of extraction conditions [36,37]. Recently we determined that in extracts of suspension cultured lymphocytes (cell line DG-75) as much as 60-65 o/, of the actin is in an unpolymerized form [39].…”
Section: Discussionmentioning
confidence: 99%
“…Biochemically, it can be measured by comparing the quantity of actin that resists triton extraction to total cellular actin. 6 The fluorescence-based methods of FRAP and PAF can also be used to estimate the polymer fraction. In FRAP, fluorescently derivatized actin is introduced to cells either through microinjection or expression, and a laser is used to rapidly photobleach a region of the cell.…”
Section: Polymer Fractionmentioning
confidence: 99%
“…6 This is made possible in many cells by the sequestering protein thymosin b4, which binds in a 1:1 complex with monomers and prevents their assembly into filaments. Thymosin b4 inhibits nucleotide exchange on bound monomers, but also has a 100-fold higher affinity for ATP-bound monomers than ADP-bound monomers, and therefore generally binds monomers after they have exchanged ADP for ATP.…”
Section: The Influence Of Thymosin B4mentioning
confidence: 99%
“…All the Pq-SO crude a-actinin fractions also contained sizable quantities of a 42,000-dalton polypeptide that migrated at the same rate as actin (Figure 67). Previous studies have shown that fibro blasts (Bray and Thomas, 1975;Perdue, 1973;Yang and Perdue, 1972) and brush borders (Tilney and Mooseker, 1971) contain actin. The Pq-SQ crude a-actinin fractions from brush borders and fibroblasts also contain and small amounts of a 30,000-dalton polypeptide that may be tropomyosin (Figure 67).…”
Section: Sps Polyacrylamide Gel Electrophoresis Of Chick Embryo Fibromentioning
confidence: 99%
“…Because both actin (Bray and Thomas, 1975;Perdue, 1973;Yang and Perdue, 1972) and myosin (Adelstein et , 1972;Ostlund et al , 1974) have been purified from fibroblasts, it seems likely that the 42,000…”
Section: Sps Polyacrylamide Gel Electrophoresis Of Chick Embryo Fibromentioning
confidence: 99%